Infection of Triatoma guasayana, Triatoma sordida and Triatoma infestans by Trypanosoma cruzi from a naturally infected opossum. - Schweigmann, N. (1997)
Fil:Schweigmann, N. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.